Durian rind soda-anthraquinone pulp and paper: effects of elemental chlorine-free bleaching and beating - Masrol, S.R; Ibrahim, M.H.I; Adnan, S; Abdul Raub, R; Sa’adon, A.M; Sukarno, K.I; Yusoff, M.F.H (Forest Research Institute Malaysia, 2018)
A study was conducted to investigate the preliminary characteristics of soda-anthraquinone (soda-AQ) durian rind waste pulp and paper with the effects of elemental chlorine-free (ECF) bleaching and beating revolutions. Pulping was carried out using rotary digester with 0.1% antraquinone, 20% active alkali (NaOH), cooking time of 120 min and temperature of 170 °C. ECF bleaching with chlorine dioxide – alkali extraction – chlorine dioxide – alkali extraction – peroxide sequence and beating in the range of 0 to 1000 revolutions were applied to the unbeaten and unbleached pulp. ECF bleached pulp produced soda-AQ durian rind paper with greater tensile index, burst index, tear index, number of folds, brightness and scattering coefficients, but with slightly lower opacity compared with paper made from unbleached pulp. The results also showed that beating revolutions improved the overall physical and mechanical characteristics of durian rind soda-AQ pulp. Bleaching and beating enhanced the durian rind soda-AQ pulp fiber-to-fiber bonding and strength. Durian rind has potential characteristics as promising new material for papermaking.